Randomized, double-blind, placebo-controlled trial of oral aloe vera gel for active ulcerative colitis. - Langmead, L; Feakins, R; Goldthorpe, S; Holt, H; Tsironi, E; De Silva, A; Jewell, D; Rampton, D (2004)
BACKGROUND: The herbal preparation, aloe vera, has been claimed to have anti-inflammatory effects and, despite a lack of evidence of its therapeutic efficacy, is widely used by patients with inflammatory bowel disease. AIM: To perform a double-blind, randomized, placebo-controlled trial of the efficacy and safety of aloe vera gel for the treatment of mildly to moderately active ulcerative colitis. METHODS: Forty-four evaluable hospital out-patients were randomly given oral aloe vera gel or placebo, 100 mL twice daily for 4 weeks, in a 2 : 1 ratio. The primary outcome measures were clinical remission (Simple Clinical Colitis Activity Index <!--= 2), sigmoidoscopic remission (Baron score </= 1) and histological remission (Saverymuttu score </= 1). Secondary outcome measures included changes in the Simple Clinical Colitis Activity Index (improvement was defined as a decrease of -->/= 3 points; response was defined as remission or improvement), Baron score, histology score, haemoglobin, platelet count, erythrocyte sedimentation rate, C-reactive protein and albumin. RESULTS: Clinical remission, improvement and response occurred in nine (30%), 11 (37%) and 14 (47%), respectively, of 30 patients given aloe vera, compared with one (7%) [P = 0.09; odds ratio, 5.6 (0.6-49)], one (7%) [P = 0.06; odds ratio, 7.5 (0.9-66)] and two (14%) [P < 0.05; odds ratio, 5.3 (1.0-27)], respectively, of 14 patients taking placebo. The Simple Clinical Colitis Activity Index and histological scores decreased significantly during treatment with aloe vera (P = 0.01 and P = 0.03, respectively), but not with placebo. Sigmoidoscopic scores and laboratory variables showed no significant differences between aloe vera and placebo. Adverse events were minor and similar in both groups of patients. CONCLUSION: Oral aloe vera taken for 4 weeks produced a clinical response more often than placebo; it also reduced the histological disease activity and appeared to be safe. Further evaluation of the therapeutic potential of aloe vera gel in inflammatory bowel disease is needed.